Utilization of pH-driven methods to fortify nanoemulsions with multiple polyphenols - Hualu Zhou; Bingjing Zheng; David Julian McClements (Food Science and Human Wellness)
Simple but effective methods are required to incorporate multiple bioactive polyphenols into delivery systems to increase their dispersibility, stability and bioavailability. We developed and tested three pH-driven protocols for creating nanoemulsions loaded with multiple lipophilic polyphenols. These protocols differed in how the different polyphenols were incorporated into the nanoemulsions. The impact of these three methods on the formation, properties, and gastrointestinal fate of nanoemulsions loaded with curcumin, resveratrol, and quercetin was investigated. The three methods produced nanoemulsions with similar initial particle properties: droplet diameters (0.15, 0.16, and 0.15 μm) and zeta-potentials (–59, –58, and –58 mV), respectively. However, the average encapsulation efficiencies (82%, 88%, and 61%), gastrointestinal stabilities (83%, 97%, and 29%) and bioaccessibilities (77%, 90%, and 73%) for curcumin, resveratrol, and quercetin were somewhat different. In particular, more quercetin degradation occurred using the approach that held it under alkaline conditions for extended periods. In general, the pH-driven method provides researchers with a versatile approach of incorporating multiple polyphenols with different characteristics into functional food and beverages using a simple and inexpensive method.